2015
DOI: 10.1002/jctb.4626
|View full text |Cite
|
Sign up to set email alerts
|

Coated nickel foam electrode for the implementation of continuous electro‐Fenton treatment

Abstract: BACKGROUND: Electro-Fenton technology has already demonstrated its ability to degrade organic pollutants. In this treatment hydroxyl radicals are formed due to the reaction of the iron catalyst along with in situ electrogenerated H 2 O 2 . However, one of the main limitations of this system is the iron released in the treated effluent. Therefore, retention of iron is required, and in this study, the use of a new cathode in which the iron is fixed on nickel foam is proposed as a solution to the electro-Fenton t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The authors concluded that new cathode is a suitable alternative for the treatment of colored wastewater by continuous electro-Fenton treatment. Similar studies have been also reported [15,16], showing that Ni-foam cathode is suitable for the treatment of colored wastewater by continuous electro-Fenton treatment.…”
Section: A D V a N C E D O N L I N E A R T I C L Esupporting
confidence: 82%
“…The authors concluded that new cathode is a suitable alternative for the treatment of colored wastewater by continuous electro-Fenton treatment. Similar studies have been also reported [15,16], showing that Ni-foam cathode is suitable for the treatment of colored wastewater by continuous electro-Fenton treatment.…”
Section: A D V a N C E D O N L I N E A R T I C L Esupporting
confidence: 82%
“…Scanning electron microscopy (SEM) images show that Ni foam ( Figure 3 a) maintained its three-dimensional porous structure after the reaction ( Figure S1 ), which is beneficial for the mass transfer of air. 22 However, its surface morphology changed dramatically as a result of chemical reaction. As demonstrated in Figure 3 b,c, the original Ni foam featured smooth surface in both microscale and nanoscale.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is likely that the above phenomenon could be attributed to the following Fenton-like reaction pathway. First, nickel foam played an important role to react with dissolved O 2 to produce • O 2 – through eq and then • O 2 – can react with H + to produce H 2 O 2 , through eq . Then, Fe 2+ acted as the catalyst and initiated the decomposition of H 2 O 2 to generate the highly reactive • OH to degrade MB, which can be described as follows In the meantime, on the basis of the standard electrode potentials of Ni 2+ /Ni and Fe 3+ /Fe 2+ pairs (eqs and ), Ni foam could promote the cycling of Fe 3+ /Fe 2+ through eq .…”
Section: Results and Discussionmentioning
confidence: 99%
“…1a) displayed a semi-circular part at high frequencies and a long straight line with an angle of approximately 45 • to the real axis at low frequencies, which evidenced a limited diffusion process (Dong et al, 2012;Kamyabi and Hajari, 2016). The diameter of the semicircular segment (depressed loop) is equivalent to the electron or charge transfer resistance (R ct ) (Bocos et al, 2016a), which indicates the kinetics of electron/charge transfer of the redox reactions at the electrode interface. Smaller R ct values typically reflect faster charge-transfer kinetics (Mann et al, 2022).…”
Section: Preparation Of Cb/ptfe Electrode: Influence Of the Binder Lo...mentioning
confidence: 99%
“…Despite the promising activity and stability of powder catalysts, some of the latest works in this field have been addressed to the development of bifunctional electrodes with electroactive properties for H 2 O 2 generation and catalytic activity to trigger Fenton reactions (Ganiyu et al, 2018;Garrido-Ramírez et al, 2016;Jiang et al, 2016). The manufacture of bifunctional cathodes is mainly based on the incorporation of active catalytic phases onto different types of conductive supports, such as metallic macroscopic structures (Choe et al, 2021;Do et al, 2017;Bocos et al, 2016a), or MOFs (Dong et al, 2021) and carbonaceous materials (Huong Le et al, 2019;Liu et al, 2018). However, carbonaceous materials, including graphite, carbon felts/clothes/fibres or carbon blacks, have been reported the most suitable ones as they gather the most favorable characteristics for their application in electrochemical systems (high conductivity, commercial availability, low-cost and sustainability) (Pérez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%